2022
DOI: 10.3390/diagnostics12081829
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Model for the Prediction of Severe Liver Fibrosis in Adult Patients with Type II Diabetes Mellitus

Abstract: Background and Objectives: Non-alcoholic fatty liver disease (NAFLD)-related severe liver fibrosis is associated with a higher risk of progressing to decompensated cirrhosis and hepatic failure and developing NAFLD-related hepatocellular carcinoma (HCC), particularly in populations with diabetes. Our pilot study aims to evaluate the performances of various noninvasive methods in predicting liver fibrosis in a population of patients with diabetes and to establish a new scoring system for the prediction of sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…The most common direct measure of insulin resistance is the high insulin/ normoglycaemic clamp (HEC) technique, which is invasive, complex and impractical. Calapod et al (15) previously developed a Logsitic regression model using HOMA-IR to predict the development of severe liver fibrosis in diabetic patients. However, HOMA-IR is susceptible to the accuracy of insulin measurements and is poorly reproducible (37).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common direct measure of insulin resistance is the high insulin/ normoglycaemic clamp (HEC) technique, which is invasive, complex and impractical. Calapod et al (15) previously developed a Logsitic regression model using HOMA-IR to predict the development of severe liver fibrosis in diabetic patients. However, HOMA-IR is susceptible to the accuracy of insulin measurements and is poorly reproducible (37).…”
Section: Discussionmentioning
confidence: 99%
“…A growing number of studies have demonstrated a positive correlation between insulin resistancerelated indexes and the degree of liver fibrosis (10,11), However, most previous studies were still limited to demonstrating that insulin resistance may be a risk factor for altered liver stiffness (12-14). Calapod et al (15) previously used homeostasis model assessment of insulin resistance (HOMA-IR) to develop a Logsitic regression model for predicting the development of severe liver fibrosis in diabetic patients. However, this study, which focused first on participants with NAFLD, not only failed to quantitatively fit liver stiffness but also had unsatisfactory predictive performance as a conventional predictive model.…”
Section: Introductionmentioning
confidence: 99%